Diversidad de quirópteros en bosques inundables y no inundables en la comunidad de “San Pablo de Cuyana” 2022 - Levy Silva, Raysa Lohana (2024)
The diversity of bats in the Amazon, particularly in the flooded and non-flooded forests, is limited. Identifying key species for ecological balance is challenging due to the lack of precise information. Therefore, it is necessary to identify the species inhabiting these areas and their distribution to address conservation challenges. This research was conducted in the flooded and non-flooded forests of 'San Pablo de Cuyana', located in the District of San Juan Bautista, Province of Maynas, Department of Loreto. The study took place between August 2022 and August 2023. The general objective was to determine the bats composition using mist nets, following the methodology proposed by Kunz and Kurta (1988). The species were identified with the aid of specialized bibliography, and the data were processed using EstimateS v. 9.0 and PAST 4 software. We found a total of 248 bats from 34 species. In the flooded forests, 70 individuals from 22 species were recorded, while in the non-flooded forests, 178 individuals from 26 species were captured. The specific diversity was lower than expected according to non-parametric indices; the Phyllostomidae family was the most abundant, followed by Vespertilionidae and Molossidae. The Stenodermatinae subfamily was the most abundant in relative terms, with the most common species being Artibeus planirostris, Carollia perspicillata, and Glossophaga soricina, while other species showed low relative abundance.